Effect of fertilization on cacao (Theobroma cacao L) seedlings in the southwest of Colombia. - Quiñones-Cabezas, Joany Alexandra; Quiñones-Quiñones, José Luis; Ballesteros-Possú, William (Revista de Ciencias Agrícolas, 2024)
Inadequate understanding of the meaning of cocoa seedlings fertilization during the nursery stage is a significant problem in the performance and profitability of cacao crops, as it negatively affects cacao yield. Therefore, it is crucial to make adequate fertilization plans and, on the other hand to replenish the nutrients extracted and preserve soil health. This study was conducted to evaluate the effect of different doses of N, P, K, Ca and Mg fertilizers on the growth and development of cocoa (Theobroma cacao L.,) seedlings (FEAR-5), under nursery conditions. A completely randomized design was used, with five treatments and three replications. Treatments were defined according to fertilization recommendations for cocoa seedlings (2 to 6 months old) (i.e., N 2.4g; P 0.6g; K 2.4g; Ca 2.3g; and Mg 1.1g) with this we came up with five treatments based on soil analysis: Treatments: T1= recommended fertilization, T2= based on a soil analysis and the addition of 7 g Ca and 3.2 g Mg; T3= 50% of recommended fertilization; T4= 150% of recommended fertilization; and T5= no fertilizer application. Our results indicate that the plants subjected to T2 showed better performance in the variables plant height, stem diameter, leaf area, number of leaves, leaf area, fresh and dry weight of the stem, fresh and dry weight and total fresh and dry weight of the seedlings. In economic terms, T4 had the highest costs. The highest profitability was recorded by T5, despite the low performance in the physiological variables.